Creatine may improve performance during short bursts of activity - Wagner, H.; Leenders, N. (1999)
New research suggests that the dietary supplement creatine may enhance the performance of elite male swimmers during short-distance swims. Researchers at Ohio State University found that male swimmers who took creatine for two weeks improved their time by an average of 0.73 seconds during a 50-meter swim. However, female swimmers in the same study did not appear to benefit from creatine supplementation. "This is one of the few studies that really looks at the effects of creatine in males and in females," said Nicole Leenders, co-author of the study and a postdoctoral researcher in Ohio State`s School of Physical Activity and Educational Services. But the improvement in the male swimmers` speed became apparent only after almost two weeks of taking creatine. The body uses phosphocreatine during high-intensity exercise, when the muscles need a quick burst of energy. Phosphocreatine restores ATP, a compound that serves as fuel for muscles. Creatine and its derivative, phosphocreatine, occur naturally in the human body. Phosphocreatine is a high-energy compound necessary for muscle contraction. Some people take synthetic forms of creatine in hopes of enhancing muscle performance. After it is ingested, stores of both creatine and phosphocreatine in the muscle can increase. The study appeared in a recent issue of the International Journal of Sport Nutrition. Leenders and her colleagues evaluated the performance of 18 men and 14 women who were members of Ohio State`s swim team. Half of the men and half of the women took creatine. Each athlete who took creatine was paired with a swimmer of the same gender who received a placebo. All swimmers received the placebo during the first two weeks of the four-week study. During the final two weeks, one partner took creatine supplements. These athletes received 20 grams of creatine each day for the first six days. Previous studies have suggested that taking 20 grams of creatine for five or six days results in an increase in both creatine and phosphocreatine concentration in the muscle. The swimmers received 10 grams of creatine each day for the final eight days of the study. The subjects took the creatine supplements and placebos before and after morning and afternoon practices. The researchers assessed each swimmer twice a week during the study -- once during a series of six 50-meter laps and once during a series of 10 25-yard laps. During the 50-meter laps, each swimmer had three minutes to complete a lap and recover. That is, if a swimmer completed the lap in 30 seconds, he or she would have two-and-a-half minutes to rest before starting the next lap. During the 25-yard laps, each swimmer had one minute to complete the lap and recover. The nine men who received creatine improved their time by an average of 2 percent in the 50-meter swim. However, the increase in average swimming speed for the male swimmers was only notable after 13.5 days of creatine supplementation, according to Leenders. Five of the nine male swimmers who received the placebo also showed some improvement in speed. "For elite male swimmers, the seemingly small decrease in time could mean the difference between winning a competition and failing to qualify for that competition," Leenders said. Neither the male nor the female swimmers showed improvement in the 25-yard swims. "This could be related to the short exercise time and a shorter recovery period for the muscles," Leenders said. In other words, the muscles may not have had enough time to re-synthesize their creatine and phosphocreatine stores. While this study suggested that taking supplemental creatine does have a cumulative effect, Leenders hesitates to recommend it to athletes -- elite or otherwise. "There are many other steps that will help a person improve athletic performance," she said. "Appropriate training and the right diet can get a person into better condition before he even thinks about taking supplements." The research was funded by the sport science and technology committee of the United States Olympic Committee and United States Swimming in Colorado Springs, Colo.